Acceptability of counselling and testing for HIV infection in women in labour at the University College Hospital, Ibadan, Nigeria (2011)
Background: Many patients are referred to labour ward as emergencies, and therefore do not benefit from the antenatal HIV counselling and testing and treatment offered to registered patients. Objective: To assess the acceptability and suitability of offering HIV counselling and testing to women of unknown HIV status presenting in labour. Methods: A cross-sectional study comprising counselling and obtaining consent for HIV testing among 104 unregistered patients who presented in labour over a 3-month period. Rapid and enzyme-linked immunosorbent assay screening was performed for 90 consenting respondents. Reactive results were confirmed by Western blot. Appropriate therapy was instituted. Results: Acceptance rate for HIV testing was 86.5%, prevalence of HIV was 6.7%. Women of lower educational status were more likely to accept testing in labour (OR: 0.3; 95% CI: 0.1-0.7; p=0.01); age, parity, occupation and knowledge of HIV had no influence. Most women (66.3%) had satisfactory knowledge of HIV. No one admitted to feeling coerced to test in fear of being denied care. Most refusals for screening were to avoid needle pricks (28.6%). Compared to ELISA screening test, specificity of the rapid test was 100%, sensitivity 85.7%, positive predictive value 100% and negative predictive value 98.8%. Attitude to testing was maintained on post-partum re-evaluation. Conclusion: The prevalence of HIV amongst unregistered parturients showed the importance of offering point-of-care HIV testing and intervention, especially in an environment where antenatal clinic attendance is poor. Rapid testing appeared to be acceptable and feasible in labour to prevent the mother-to-child transmission of HIV.